ANALISIS PENERAPAN PSAK NO. 46 TERHADAP PAJAK TANGGUHAN PT. MERAPI PRODUCTION SURABAYA - SISWIANINGRUM, NOVI PURI; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
PT. Merapi Production is a manufacturing company which is intended to gain maximum profit in their business field. This research is meant to find out how the company should implement the Financial Accounting Standard Statement (PSAK) No. 46 on deferred tax in the financial statements. Implementation of PSAK No. 46 has using asset and obligation. Temporary difference occurs because of recognition and the use of different method or estimation between the accounting purposes and taxation. The method is qualitative descriptive, meanwhile the data collection has conducting observation / survey, interview, documentation and literature study. The recording of deferred tax value has been obtained from classification of account recognition on the allowed balance sheet according to the commercial based on difference DTA (Deferred Tax Asset) and DTL (Deferred Tax Liability) then it is multiplied by the tax rate deferred tax in accordance with the taxation law. The result of the research shows that PT. Merapi Production has not implemented the PSAK No. 46 on the recording and financial statement yet. After the PSAK No. 46 has been implemented the that financial statement increases compared to the financial statement which has not implemented the PSAK No. 46. Keywords: Temporary Different, Deferred Tax, Deferred Tax Asset, Deferred Tax Liability.